How do Companies Invest in Corporate Social Responsibility? An Ordonomic Contribution for Empirical CSR Research - Matthias Georg Will; Stefan Hielscher (Administrative Sciences, 2014)
This paper takes both a conceptual and an empirical approach to answer the question as to how Corporate Social Responsibility (CSR) can be connected to the company’s role as an agent of social value creation when it operates within an imperfect institutional framework of market competition. To develop a functional design for an empirical study, we draw on the concept of ordonomics, which provides a heuristics for responsible business activities in society. Drawing on ordonomics, we devise three questions: Referring to action responsibility we ask in which CSR activities companies do invest in their day-to-day business. Referring to governance responsibility we ask as to how companies realize win-win solutions through strategic commitments. In addition, with regard to discourse responsibility we ask in which stakeholder dialogues companies engage in order to discuss and find functional rules for organizing win-win solutions. In our empirical study, we reveal insights into the micro-level analysis of the CSP-CFP link and generate several new questions to be the subject of future research.